1992
DOI: 10.1084/jem.175.1.305
|View full text |Cite
|
Sign up to set email alerts
|

Donor major histocompatibility complex (MHC) peptides are presented by recipient MHC molecules during graft rejection.

Abstract: SunlmaryPeptides from donor major histocompatibility complex (MHC) molecules were examined for their activation of allogeneically primed T cells. After immunization with either allogeneic spleen cells or a skin allograft, primed T cells proliferate in response to peptides derived from polymorphic regions of a and B chains of dass II allo-MHC molecules. The results demonstrate that presentation of donor-MHC peptides by host-derived antigen-presenting cells is a common event in vivo. Thus, self-restricted T cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
119
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(124 citation statements)
references
References 21 publications
5
119
0
Order By: Relevance
“…The direct recognition pathway involves recognition of allogeneic MHC/peptide complexes expressed on dendritic cells (passenger leukocytes) of the donor by T cells of the recipient. MHC molecules of the donor may directly present peptides to the T cells of the recipient (31). It has been proposed that molecular mimicry is the basis of this recognition (29,52).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The direct recognition pathway involves recognition of allogeneic MHC/peptide complexes expressed on dendritic cells (passenger leukocytes) of the donor by T cells of the recipient. MHC molecules of the donor may directly present peptides to the T cells of the recipient (31). It has been proposed that molecular mimicry is the basis of this recognition (29,52).…”
Section: Discussionmentioning
confidence: 99%
“…However, stimulation of T cells of the recipient by donor APCs that may lack costimulatory molecules will lead to anergy, reducing the significance of this response after the early post-transplantation period (60 -64). The indirect recognition pathway involves presentation by APC of the recipient to T cells of the recipient of epitopes comprised of MHC molecules of the recipient and antigenic peptides derived from MHC Ags of the donor (27)(28)(29)(30)(31)(32)(33)(34)(35). The later should be available in high quantities in the graft, because of cell destruction at the site of the graft and possible shedding of MHC molecules.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies, along with others using MHC class I (CI)-and class II (CII)-deficient donors (11), suggested that indirect antigen presentation is an important pathway mediating MHC CI-and MHC CII-disparate allograft rejection. Additionally, experiments using donor-derived peptides to stimulate alloreactive T cells and donor tissues derived from MHC-deficient mice confirmed indirect antigen presentation as an important mechanism in the rejection of allogeneic organs and tissues (4,5,9,(12)(13)(14)(15)(16)(17)(18). However, the lack of an in vivo model system restricted to recognizing directly presented donor alloantigen has made it difficult to ascertain the unique role of direct antigen presentation in allograft rejection.…”
Section: Introductionmentioning
confidence: 99%